Views and experiences of nurse practitioners and medical practitioners with collaborative practice in primary health care – an integrative review - Schadewaldt, Verena (BioMed Central, 2013)
BACKGROUND: This integrative review synthesises research studies that have investigated the perceptions of nurse practitioners and medical practitioners working in primary health care. The aggregation of evidence on barriers and facilitators to working collaboratively and experiences about the processes of collaboration is of value to understand success factors and factors that impede collaborative working relationships. METHODS: An integrative review, which used systematic review processes, was undertaken to summarise qualitative and quantitative studies published between 1990 and 2012. Databases searched were the Cochrane Library, the Joanna Briggs Institute Library, PubMed, Medline, CINAHL, Informit and ProQuest. Studies that met the inclusion criteria were assessed for quality. Study findings were extracted relating to a) barriers and facilitators to collaborative working and b) views and experiences about the process of collaboration. The findings were narratively synthesised, supported by tabulation. RESULTS: 27 studies conducted in seven different countries met the inclusion criteria. Content analysis identified a number of barriers and facilitators of collaboration between nurse practitioners and medical practitioners. By means of data comparison five themes were developed in relation to perceptions and understanding of collaboration. Nurse practitioners and medical practitioners have differing views on the essentials of collaboration and on supervision and autonomous nurse practitioner practice. Medical practitioners who have a working experience with NPs express more positive attitudes towards collaboration. Both professional groups report concerns and negative experiences with collaborative practice but also value certain advantages of collaboration. CONCLUSIONS: The review shows that working in collaboration is a slow progression. Exposure to working together helps to overcome professional hurdles, dispel concerns and provide clarity around roles and the meaning of collaboration of NPs and MPs. Guidelines on liability and better funding strategies are necessary to facilitate collaborative practice whether barriers lie in individual behaviours or in broader policies.